Spectrophotometric Determination of H2O2 in Disinfectant Drug Water by Dibromo-p-methyl-arsenazo Oxidation - Hu, Wei-Hua; Zhai, Qing-Zhou (Asian Journal of Chemistry, 2013)
By using the property that hydrogen peroxide oxidizes dibromo-p-methyl-arsenazo to produce a decolouring reaction and hemoglobin has catalytic action, this paper proposed a new method for decolouring spectrophotometric determination of trace hydrogen peroxide. In pH 5.2 CH3COOH-CH3COONa buffer medium, the maximum absorption wavelength is at 400 nm. Beer’s law is obeyed over the range of 2.47 × 10-5-1.23 × 10-4 mol L-1 for the concentration of H2O2. The method was successfully used in the determination of hydrogen peroxide in disinfectant drug water sample. The relative standard deviation of 13 determinations was 3.01 % and the addition standard recovery of method was 103.90 %.